DAMPAK POLITIK PRAKTIS ASN DALAM PILKADA 2020 DI DESA FATUMUTI, KECAMATAN NOEMUTI, KABUPATEN TIMOR TENGAH UTARA - Oscar A.T. Berkanis (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study examines the impact of practical politics on Civil Servants (ASN) in the 2020 Regional Head Election (Pilkada) in Fatumuti Village, Noemuti Subdistrict, North Central Timor Regency. The involvement of ASN in political contestation has become a critical issue as it affects bureaucratic neutrality, work professionalism, and the quality of public services. The background of this research highlights the shifting role of ASN, who are supposed to remain neutral, but are often drawn into the dynamics of practical politics due to pressure and the interests of political elites. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The informants consist of ASN who directly experienced the impact of practical politics during and after the election. The data were analyzed systematically through reduction, presentation, and conclusion drawing to provide an empirical picture of the situation in the field. The findings reveal that practical politics in the 2020 election resulted in two main patterns: revenge politics and reward politics. ASN perceived as being in opposition to the new authorities were often subject to job transfers, delayed promotions, or removal from strategic positions. Conversely, those who supported the winning candidates were rewarded with promotions or positions, not always based on competence. This situation created bureaucratic injustice and weakened the merit system principle. Another impact identified was the obstruction of career development, decreased work motivation, and a sense of insecurity among ASN. Practical politics also reduced the quality of public services, as appointments were no longer based on expertise but on political closeness. This not only harmed ASN individually but also disadvantaged the broader community, who are entitled to professional and quality public services. The study concludes that practical politics worsens local governance, undermines bureaucratic neutrality, and threatens the quality of local democracy. Therefore, it recommends strengthening regulations on ASN neutrality, consistent implementation of the merit system, and enhancing the understanding of public administration ethics. These measures are essential to rebuild a neutral, professional, and integrity-based bureaucracy oriented toward the public interest